A Comparative Performance Analysis of AODV and DSR Routing Protocols for Vehicular Ad-hoc Networks (VANETs) (International Journal of Engineering and Computer Science, 2015)
Vehicular ad hoc networks (VANETs) are the specific class of Mobile ad hoc networks (MANETs). Since vehicles tend to move in a high speed, the network topology is rapidly changed. The performance of communication between vehicles depends on how better the routing takes place in the network. Routing of data depends on the routing protocols which are being used in network. In this paper we analyse and compare the performance of two reactive routing protocols Dynamic Source Routing (DSR) and Ad hoc On Demand Distance Vector (AODV) in terms of three performance metrics like throughput, network load and end-to-end delay with different number of mobile nodes (100, 150, 200 and 250) with constant speed 10m/s. We employed OPNET Modeller v14.5 for the performance analysis of two reactive routing protocols (AODV, DSR). OPNET modeller 16.0 is a network simulator environment which is used for simulations of both wireless and wired networks. A conclusion is drawn on the comparison between these two routing protocols with performance metrics like network load, end-to-end delay and throughput on the basis of results derived from simulation.